Changes in the Plantarflexion Moment Arm of the Achilles Tendon Following Total Ankle Arthroplasty. Issue 4 (22nd October 2020) - Wade, Francesca E.; Lewis, Gregory; Horne, Andrea H.; Hickox, Lauren; Aynardi, Michael C.; Juliano, Paul J.; Aydogan, Umur; Piazza, Stephen J.
Category: Ankle; Ankle Arthritis Introduction/Purpose: Deficits in ankle joint kinetics following total ankle arthroplasty (TAA) may be attributed to a reduction in the force-generating capacity of ankle joint muscles, but it is also important to consider the alterations to joint structure that may accompany this procedure. One key parameter indicative of joint structure with the potential to be influenced by TAA is the plantarflexion moment arm of the Achilles tendon (ATma). ATma is an indicator of the potential for the tendon force to produce plantarflexion moment that is determined by the three-dimensional line of action of the tendon relative to the ankle joint axis. The purpose of this study was to assess pre-to-post TAA changes in ATma; we hypothesized that pre- and post-TAA moment arms would not be different. Methods: We tested 10 TAA patients (age at surgery: 62.86 +- 9.72 y; height: 1.72 +- 0.08 m; body mass: 97.81 +- 20.89 kg) at pre-operative (˜ 1 mo pre) and post-operative (˜6 mo post) visits. All procedures involving testing of human subjects were approved by the Penn State Hershey Medical Center Institutional Review Board. ATma were measured using a method that combined ultrasound imaging of the tendon with 3D motion tracking of both the ultrasound probe and the ankle joint. The tendon and joint axis were located during trials in which the patients were seated with the knee extended while the ankle joint was voluntarily rotated in the sagittal plane. We also examined sagittal-plane weightbearing radiographs (pre- and post-op) to determine the AP distance from the center of the talar dome to the posterior margin of the calcaneus. Pre- and post-op ATma were compared using a paired t-test and regression. Results: No significant mean differences were found between post-op ATma and pre-op ATma (p = 0.360). Despite this, some patients were found to have large differences between pre- and postoperative ATma. For example, participants 1, 3, and 8 exhibited changes of -54.22%, +64.14% and +123.98% (pre-to-post) respectively (Figure 1). A moderate correlation between pre- and post-op ATma was found (r2 = 0.461, p = 0.031), indicating that only 46.1% of the variance in post-op ATma was explained by pre-op ATma (Figure 1). The normalized AP distance measured from the radiographs did not significantly change on average pre- to post-TAA (p = 0.561), and we found the change in this distance to correlate with the change in ATma (r2 = 0.370, p = 0.062). Conclusion: This is the first investigation of whether TAA alters ATma. Our results supported our hypothesis that pre-operative ATma predicts post-operative ATma. However, our hypothesis is supported only when the mean differences are considered, as there were sizeable differences for individuals. Despite a non-significant average change in ATma following TAA, at the individual level substantial changes in ATma were observed in seven of the 10 patients. Change in ATma was only partly explained by change in the AP position of the talar dome. Change in ATma has potential consequences for function in terms of ankle plantarflexor strength and walking velocity.